Pengaruh Reputasi Merek dan Kesadaran Merek Terhadap Keputusan Pembelian Produk Air Minum NU Berkah - Ahmad Yusuf Abdi Firdaus; Lingga Yuliana (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
The purpose of this study was to examine the effect of brand reputation and brand awareness on consumer decisions to purchase bottled drinking water products, with a special emphasis on the NU Berkah brand. The research method used in this study is quantitative. Purposive sampling was used in the sampling procedure. This survey involved a total of 99 respondents. Men and women aged between 17 and 57 years who live in Indonesia and use NU Berkah brand bottled drinking water (AMDK) became respondents. The data source distributed questionnaires via Google Form to obtain primary data. In this study, closed questions with Likert scale response criteria strongly disagree, disagree, agree, and strongly agree were used. By using the SmartPLS tool version 4.1.0.0, the data analysis method used Partial Least Squares. The findings of the study indicate that reputation and brand awareness have a beneficial and significant impact on consumer decisions to purchase.